2020
DOI: 10.1177/0361198120919749
|View full text |Cite
|
Sign up to set email alerts
|

Asphalt Mixture Quality Acceptance using the Hamburg Wheel-Tracking Test

Abstract: This paper investigates the applicability of the Hamburg wheel-tracking test (HWTT) for asphalt mixture quality acceptance using laboratory-compacted specimens and field-compacted specimens. Density distribution functions for rut depths, stripping inflection points, and rutting resistance index (RRI) values used in the HWTT were obtained for mixtures with different nominal maximum aggregate size (NMAS) values and binder performance grades. Clear distinctions among the rut depth distributions for the high-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Accordingly, better rutting performance for coarser gradations was reported by Larrian and Tarefder [11]. Batioja et al [12] studied the potential of Hamburg as a quality assurance test to be implemented in the state of Indiana. To this end, the effects of binder grade, NMAS, and testing temperature on both field cores and plant produced lab compacted samples were investigated through the rutting resistance index (RRI).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Accordingly, better rutting performance for coarser gradations was reported by Larrian and Tarefder [11]. Batioja et al [12] studied the potential of Hamburg as a quality assurance test to be implemented in the state of Indiana. To this end, the effects of binder grade, NMAS, and testing temperature on both field cores and plant produced lab compacted samples were investigated through the rutting resistance index (RRI).…”
Section: Introductionmentioning
confidence: 93%
“…It was observed that in all four mixtures, the field cores accumulated lower rut depth as compared to the gyratory compacted samples in the lab. However, results reported in [12] showed better rutting resistance in plant-produced, laboratory-compacted (PPLC) specimens. The significant effect of sample type such as field core, PPLC and labproduced, lab-compacted (LPLC) has been reported in other studies [25].…”
Section: Introductionmentioning
confidence: 97%
“…Several research studies have been conducted to identify the key factors that significantly affect the rutting and stripping potential of AC materials. Aggregate type and gradation, performance grade binder (PG), reclaimed asphalt pavement (RAP) content, antistripping agents, air voids content, temperature, and so forth, play a vital role in the rutting performance of AC materials (9)(10)(11)(12)(13)(14)(15)(16)(17). A study by Tarefder and Zamman revealed that air void content and aggregate gradation have a significant effect on pavement rutting performance (10).…”
mentioning
confidence: 99%